Professional Competence and Skepticism on Audit Quality - Z. D. Siahay, Adolf; C. Seralurin, Yohanes; Ervina, Melisa Triayu; Pattiasina, Victor (Advances in Managerial Auditing Research, 2023)
Purpose: This study analyzes the effect of competence and professional skepticism on audit quality among auditors at the Papua Provincial Inspectorate Office. Understanding how these internal factors contribute to audit quality is essential for improving the effectiveness of the auditing process. Research Design and Methodology: The study employed a quantitative research approach using primary data collected through questionnaires distributed to auditors at the Papua Provincial Inspectorate. The sampling technique used was purposive sampling, resulting in a sample of 32 respondents. Data were analyzed using SPSS version 26, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Findings and Discussion: The results revealed that professional competence and professional skepticism positively and significantly impact audit quality. Competent auditors demonstrated a higher ability to detect errors and ensure the accuracy of financial statements. In contrast, auditors with higher skepticism were more likely to question evidence and identify potential misstatements during the audit process. Implications: These findings highlight the importance of enhancing auditors' competence and fostering professional skepticism through continuous training and certification programs. Future research should explore additional variables influencing audit quality, such as auditor independence, ethical standards, and institutional support.